2018
DOI: 10.30548/vascfail.2.1_32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Canagliflozin on endothelial function in diabetic patients with suspected coronary artery disease: retrospective preliminary pilot study

Abstract: Background: Sodium-glucose transporter-2 inhibitor (SGLT2) is reported to have anti-atherosclerotic effects in experiment. However, the effect of SGLT2 on endothelial function (ECF) in humans is not fully investigated. Method and Results: We measured ECF in 11 diabetic patients with coronary artery disease (CAD) and poor control of diabetics (HbA1c >7%; 75 8 years old) by simultaneously measuring brachial artery flow-mediated dilation (FMD) and EndoPAT2000 (measuring RHI). FMD and RHI were measured before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The current study also revealed that daily administration of oral DAPA for 14 days decreased inflammation and its markers (LDH, CRP). These results are consistent with a previous study [ 33 ], which revealed that 100 mg canagliflozin every other day improved endothelial function in diabetic patients with suspected coronary disease through decreased markers of inflammation. Furthermore, the present study reported that AA inducing marked oxidative stress with significantly elevated MDA and reduced TAC in colonic tissue, which is in harmony with a previous study [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The current study also revealed that daily administration of oral DAPA for 14 days decreased inflammation and its markers (LDH, CRP). These results are consistent with a previous study [ 33 ], which revealed that 100 mg canagliflozin every other day improved endothelial function in diabetic patients with suspected coronary disease through decreased markers of inflammation. Furthermore, the present study reported that AA inducing marked oxidative stress with significantly elevated MDA and reduced TAC in colonic tissue, which is in harmony with a previous study [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several scholars have investigated whether glycemic control with these agents has any beneficial effects on the progression of atherosclerosis. In poorly controlled T2DM with CAD, administration of 100 mg canagliflozin for 4 wk improved HbA1c [from 9.2 (mean ± SD) ± 1.4 to 8.6 ± 1.1%, P < 0.01] and FMD[ 73 ]. In this study, none of the patients were treated with insulin.…”
Section: Functional Markersmentioning
confidence: 99%